Casual alcohol consumption is associated with less subclinical cardiovascular organ damage in Koreans: a cross-sectional study - Jeonggeun Moon; In Cheol Hwang; Kyoung Kon Kim; Woong Chol Kang; Ji-Young Cha; Young-Ah Moon (BMC, 2018)
Abstract Background Epidemiologic studies have presented protective effects of alcohol against cardiovascular (CV) events. However, such studies were performed mainly on Westerners. We investigated the effects of alcohol on the subclinical CV morbidity in healthy Koreans. Methods The coronary artery calcium (CAC) score, ankle-brachial pulse wave velocity (abPWV), and carotid intima-media thickness (cIMT) of 1004 subjects (age, years±standard deviation [SD] 53 ± 10; 72% were men) with no CV disease history were assessed. The subjects were divided into three groups based on their drinking patterns: Group 0 (abstainers), Group 1 (casual drinkers), and Group 2 (problematic drinkers; > 14 standard drinking/week for men, > 7 standard drinking/week for women). As drinking patterns can be influenced by age/sex, a regression analysis was performed in another four groups (men/women, age < 65/≥65 years). Results Group 1 exhibited lower CAC (score ± SD, 44 ± 155 vs. 13 ± 48 vs. 50 ± 159) and abPWV (cm/s ± SD, 1448 ± 284 vs. 1340 ± 190 vs. 1447 ± 245) scores and thinner cIMT (mm ± SD, 0.64 ± 0.14 vs. 0.59 ± 0.11 vs. 0.63 ± 0.13) than Groups 0 and 2 (p < 0.05 for all). Problematic drinking (odds ratio [OR]: 2.269; 95% confidence interval [CI]: 1.454-3.541) was associated with a high prevalence of CAC deposits among men aged < 65 years and casual drinking with a lower prevalence of CAC deposits (OR: 0.057; 95% CI: 0.023-0.140) among men aged ≥65 years. Conversely, problematic drinking in older women [OR: 0.117; 95% CI: 0.014-0.943) and casual drinking in younger women (OR: 0.349; 95% CI: 0.153-0.792) were associated with a lower prevalence of CAC deposits. Casual drinking was associated with a lower abPWV and thinner cIMT in the diabetes mellitus/hypertension-adjusted regression analysis. Conclusions Compared with abstinence or problematic drinking, casual drinking was associated with less severe CV organ damage in the subclinical stages in Koreans.